Analysis of Teach Like Finland's Book for The Development of Learning Strategies for Zakat Material in Islamic Senior High School - Cut Nyak Marlina; Zulfatmi Zulfatmi (DAYAH: Journal of Islamic Education, 2023)
Finland currently ranks first in the globe for quality education. The nation is known for its excellent educational system. Therefore, researchers are interested in analyzing the learning strategies contained in the Teach Like Finland book, as well as learning strategies that are applicable to zakat-related material. This objective is to develop learning strategies for zakat-related materials so that learning can be made more effective and efficient through the use of innovations and diverse approaches. This study employs the content analysis method. Several of the 33 strategies outlined in the book Teach Like Finland, such as brain rest schedules, learning on the move, celebrating their learning, leaving boundaries and offering choices, to make learning real, are suitable for teaching zakat-related material.